Strategi Dakwah IPHI Kabupaten Karanganyar dalam Meningkatkan Ukhuwah Islamiyah - Firda Rohana; Fathurrohman Husen; Puput Yanita Senja (UIN Raden Mas Said Surakarta, 2022)
Jamaah IPHI Karanganyar Regency has a different islamic organizational background, but is able to realize a harmonious, tolerant Islamic society, and is able to establish Islamic ukhuwah between pilgrims. The question is how the da'wah strategy carried out by IPHI Karanganyar Regency in maintaining and maintaining ukhuwah Islamiyah among its worshippers. This research aims to 1) find out how the IPHI da'wah strategy of Karanganyar Regency in maintaining ukhuwah Islamiyah among its worshippers 2) Knowing the effectiveness of the da'wah strategy 3) Knowing what are the driving factors and obstacles in carrying out da'wah strategies. This type of research is field research with descriptive qualitative methods. The source of this research data is primary data, namely from the interview results of the chairman of IPHI Karanganyar Regency, both education, training and da'wah, and IPHI Karanganyar pilgrims. Secondary data obtained from photo documentation of activities and documents or archives of IPHI Karanganyar Regency. Through research it is known that the da'wah strategy of IPHI Karanganyar Regency in maintaining ukhuwah Islamiyah among its pilgrims is: 1) Through three stages namely the formulation of strategy, implementation and evaluation 2) da'wah program is carried out by two methods namely oral bil method and bil p 3) IPHI management services in controlling ukhuwah Islamiyah pilgrims by instilling mutual respect and through government policy with the establishment of IPHI and the role of the community in IPHI Karanganyar Regency 4) The effectiveness of da'wah strategy carried out by IPHI Karanganyar is good, and 5) There are supporting factors and obstacles in carrying out da'wah strategies in maintaining Islamic ukhuwah among pilgrims.